Contagion and the emergence of convention in small worlds - Edward Cartwright (University of Kent, Department of Economics, 2004)
We model a simple dynamic process in which boundedly rational agents learn through their interactions with others. Of interest is to study the process of contagion where by one action 'spreads throughout the population' and becomes conventional. We vary the network of player interaction between a regular lattice and a random network allowing us to model contagion in small world networks. Through simulation results we highlight the importance of network structure on both the possibility of contagion and the rate of contagion.
Keywords: C70; C72; C62; 330; Best reply; risk dominant; contagion; small world; Lernprozess; Unternehmensnetzwerk; Prinzipal-Agent-Theorie; Soziales Netzwerk